Establishment of Normative Self-Rated Health Status Data and Association between Ideal Life Expectancy and Social Wellness of General Population in Korea - Jihye Lee; Jin-Ah Sim; Ji-Won Kim; Young Ho Yun (Elsevier, 2019)
Purpose: The purpose of this study was to establish normative data for holistic health parameters in the general Korean population and to investigate the factor associated with ideal life expectancy (ILE) among these holistic health parameters and sociodemographic variables. Methods: This study used a questionnaire to obtain self-reported physical, mental, social, spiritual, and general health status and then evaluated their association with ILE. A total of 1,241 individuals responded to the questionnaire, from which we established a multidimensional health status reference data set representing the Korean population. To explain factors associated with ILE, we stratified results by age and gender and performed multiple logistic regression of sociodemographic variables and multidimensional health status. Results: Women reported poor health status more frequently for all five health categories. The average ILE was 87.46 years versus 84.42 years of life expectancy in the general Korean population. Single marital status, higher income, and better social health were significantly associated with higher ILE. Conclusion: ILE could be a good indicator reflecting social wellness in a certain society. Comprehensive social health promotion programs can improve individuals' attitudes toward life expectancy, especially for vulnerable groups. Keywords: holistic health, life expectancy, population health, self report, socioeconomic factors